2020
DOI: 10.24925/turjaf.v8i8.1763-1772.3504
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Leonardite and Mineral Fertilizer Applications on Plant Growth and Soil Quality of Garlic (Allium sativum L.)

Abstract: Turkey is one of the major garlic producing country in the world and the significant amount of Turkey’s production has been made using a garlic variety called Taşköprü garlic (Allium sativum L.) in Kastamonu, Turkey. In order to improve the quality of garlic production, a field experiment was conducted to evaluate the effects of different doses of leonardite organic fertilizer, mineral fertilizer NPK and the mixture of both the leonardite and NPK fertilizers on the soil properties and mean performances of diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Originating from different sources, HS have different compositions and biological effects depending on their chemical structure and physicochemical properties [5][6][7]. Extracts of HS that already have industrial applications in the world are extracted from leonardites and used alone or in combination with mineral fertilizers [8][9][10]. In this way, not only are the physical properties of the soil protected and improved, but the effect of inorganic fertilizers also acquires greater efficiency-the mobility and absorption of nutrients increase, and a richer yield is obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Originating from different sources, HS have different compositions and biological effects depending on their chemical structure and physicochemical properties [5][6][7]. Extracts of HS that already have industrial applications in the world are extracted from leonardites and used alone or in combination with mineral fertilizers [8][9][10]. In this way, not only are the physical properties of the soil protected and improved, but the effect of inorganic fertilizers also acquires greater efficiency-the mobility and absorption of nutrients increase, and a richer yield is obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Control application (unapplicated fertilizer) produced the lowest grain yield in both of the cultivars. [9] revealed that marketable bean yield was higher in leonardite application compared to recommended fertilizer doses [30] reported that mineral fertilizer + leonardite application increased soil N content and garlic yield. Similar to our results, earlier studies reported that leonardite or humic acid and other manure applications increased seed yield of chickpea, faba bean, lentil and cowpea [21,5,14,10,31].…”
Section: Resultsmentioning
confidence: 99%
“…Research into the effects of leonardite amendment on arable soil and crop performance has been widely conducted, and largely positive results have been reported. For instance, leonardite application modified soil quality and increased the soil organic C (SOC) and total N contents of soil (Sarıyıldız, 2020; J. Wang et al., 2020), accompanied by increased crop yield and fertilizer utilization rate (Akimbekov et al., 2020; Akinremi et al., 2000; Sarıyıldız, 2020). Furthermore, leonardite was found to enhance tolerance to drought and P deficiency stress of specific plants (Kaya et al., 2020).…”
Section: Introductionmentioning
confidence: 99%